PERANCANGAN SISTEM INFORMASI LAPORAN PERTANGGUNGJAWABAN BAGIAN PERENCANAAN DAN KEUANGAN DI SEKRETARIAT DAERAH KABUPATEN BANDUNG - Yuyun Yunita; Muthmainnah; Candra Mecca Sufyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The accountability report is one of the important indicators to know the performance of the APBD in a government agency. The process of preparing accountability reports in the planning and finance department still uses Microsoft Excel, which still brings many obstacles. Some of these obstacles show that the planning and finance departments have not optimized today's information technology, so the production of accountability reports has not been effective. Therefore, this study aims to design an information system for accountability reporting in the Planning and Finance Department of the Regional Secretariat of Bandung Regency. Data collection techniques using qualitative methods. The method for designing the accountability report system is uses the waterfall method, which consists of five phases. The design of this information system is web-based, using flowmap modeling and data flow diagrams, and implemented with the PHP programming language and MySQL database. It is hoped that this information system will facilitate budget entry and produce accurate and understandable accounting reports. This information system is expected to facilitate recording of budgets and produce accountability reports that are accurate and easy to understand.